Cardiac Fibrosis: Cellular Effectors, Molecular Pathways, and Exosomal Roles - Jiang, Wenyang; Xiong, Yuyan; Li, Xiaosong; Yang, Yuejin (Frontiers in Cardiovascular Medicine, 2021)
Cardiac fibrosis, a common pathophysiologic process in most heart diseases, refers to an excess of extracellular matrix (ECM) deposition by cardiac fibroblasts (CFs), which can lead to cardiac dysfunction and heart failure subsequently. Not only CFs but also several other cell types including macrophages and endothelial cells participate in the process of cardiac fibrosis via different molecular pathways. Exosomes, ranging in 30–150 nm of size, have been confirmed to play an essential role in cellular communications by their bioactive contents, which are currently a hot area to explore pathobiology and therapeutic strategy in multiple pathophysiologic processes including cardiac fibrosis. Cardioprotective factors such as RNAs and proteins packaged in exosomes make them an excellent cell-free system to improve cardiac function without significant immune response. Emerging evidence indicates that targeting selective molecules in cell-derived exosomes could be appealing therapeutic treatments in cardiac fibrosis. In this review, we summarize the current understandings of cellular effectors, molecular pathways, and exosomal roles in cardiac fibrosis.